Need Analysis: Exploring The Development of an Organic Module in Teaching Organic Reaction Mechanism (ORM) - Nik Hassan, Nik Mawar Hanifah; Kamarudin, Nurzatulshima; Muhamad, Mohd Mokhtar; Talib, Othman (International Journal of Advanced Research in Future Ready Learning and Education, 2025)
Organic Reaction Mechanism (ORM) is a challenging topic in organic chemistry that students must learn meaningfully. ORM studies are expanding in various ways, yet there is still a scarcity of studies on module development incorporating the teaching and learning ORM. This paper reports the needs analysis phase of the Design and Development research (DDR) study, which aims to explore the need to develop an Organic Module for teaching ORM among experts. Note that five experts were interviewed in this phase. The data were examined using thematic analysis to meet the study’s objectives. Based on the findings, experts are having problems teaching the topic of ORM in schools. Most of them claim that students lack basic knowledge of the ORM concept, misunderstand placing the arrow correctly in the mechanism reaction and believe that ORM requires memorization. At the same time, there are not enough learning materials, such as modules appropriate for the pre-university syllabus. Most experts agreed that the ORM module should be developed to enhance and assist students’ understanding of organic mechanisms. The study implies that this module may be utilized by chemistry educators, lecturers, or teachers since the ORM module in this study is based on the pre-university syllabus.